KAJIAN TEOLOGIS TERHADAP PRAKTIK BUNUH DIRI - Adi Putra (Manna Rafflesia, 2025)
This research examines the phenomenon of suicide that is rampant in society. As Christians, it is necessary to study it in order to find the right formula to be conveyed to the congregation as a pastoral reference to prevent the massive practice of suicide in the church. By using qualitative research methods, especially literature review, the following conclusions were found. The practice of suicide is a practice that is not desired by God. Or in other words, this act is carried out according to the desires of the human heart and will, thus rejecting God's sovereignty in human life. That is why every Christian is not allowed to do this practice.